2011
DOI: 10.1371/journal.pone.0020724
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Economic Crises on Communicable Disease Transmission and Control: A Systematic Review of the Evidence

Abstract: There is concern among public health professionals that the current economic downturn, initiated by the financial crisis that started in 2007, could precipitate the transmission of infectious diseases while also limiting capacity for control. Although studies have reviewed the potential effects of economic downturns on overall health, to our knowledge such an analysis has yet to be done focusing on infectious diseases. We performed a systematic literature review of studies examining changes in infectious disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
139
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(155 citation statements)
references
References 59 publications
(96 reference statements)
7
139
0
9
Order By: Relevance
“…TB is considered to be a disease of the socially and economically disadvantaged, since its incidence is exacerbated by socioeconomic factors, inconsistent or partial treatment practices and immigration from countries in which the disease is endemic [6,9,10]. Reducing inequalities in TB incidence in Europe is, therefore, a goal that needs to be addressed, especially since the recent global financial crisis is expected to exacerbate health inequalities [11,12]. However, the relatively small contribution of TB to overall mortality and morbidity makes the statistical analysis not feasible on the individual level and an ecological study is needed.…”
mentioning
confidence: 99%
“…TB is considered to be a disease of the socially and economically disadvantaged, since its incidence is exacerbated by socioeconomic factors, inconsistent or partial treatment practices and immigration from countries in which the disease is endemic [6,9,10]. Reducing inequalities in TB incidence in Europe is, therefore, a goal that needs to be addressed, especially since the recent global financial crisis is expected to exacerbate health inequalities [11,12]. However, the relatively small contribution of TB to overall mortality and morbidity makes the statistical analysis not feasible on the individual level and an ecological study is needed.…”
mentioning
confidence: 99%
“…More than 70% of these zoonotic diseases in humans originate from wildlife (Morse et al, 2012;Van Doorn, 2014). These shifts in infectious diseases are caused by the adaptation of microorganisms to changes in human behavior, demographics, and life style (Cascio et al, 2011); changes in economic development and land use (Suhrcke et al, 2011); loss of biodiversity (Swaddle and Calos, 2008;Ostfeld, 2009); global travel (Hufnagel et al, 2004); immigration (Schmid et al, 2008); air conditioning; crowded intensive care units in large hospitals; global environmental and climate changes (Semenza et al, 2012); evolution of susceptible populations, exotic pets, exotic foods and pathogen adaptation (Casadevall et al, 2011;Price et al, 2012); as well as advances in detection techniques Allerberger, 2012;van Doorn, 2014). With industrialization of food processing, worldwide shipment of fresh and frozen food and an increased demand for fresh bagged produce foodrelated outbreaks shifted from local, often family-based, outbreaks to multistate or multicountry outbreaks, often caused by a single source (Shane et al, 2002;Tauxe, 2002;Denny et al, 2007;Nygren et al, 2013;Schmid et al, 2014;Ruppitsch et al, 2015b;Inns et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the literature on the impact of economic crisis on communicable diseases identified 37 studies, 30 of which reported worse infectious disease outcomes (Suhrcke et al, 2011). These studies report higher rates of infection due to poorer living conditions, reduce access to therapies and treatment retention as reasons for worse outcomes.…”
mentioning
confidence: 99%
“…However, it should be noted that a large number of these studies report on conditions in central and eastern European countries during the early 1990, at a time of economic and political turmoil. Studies from Germany, Japan and other OECD countries, reported fewer influenza and respiratory disease deaths during times when unemployment was high as opposed to low (Suhrcke et al, 2011). Nevertheless, a country's ability to respond to emerging risks is paramount to longterm health system goals.…”
mentioning
confidence: 99%